Арт - терапия как способ психокоррекции социального взаимодействия детей с особыми образовательными потребностями - Шмидт, В.В. (My University, 2016)
The article describe the effectiveness of the exercise with elements of art – psycho therapy work with children special educational needs. The use of art – therapy in a child psychologist helps to overcome communication barriers and psychological defenses in children of preschool. The author presents his own experience with art – therapy to develop fine motor skills, perception and emotional – personal sphere communicative and social , living attainments for children with special needs
Keywords: children with special needs; art – therapy; emotional disorders; socialization; psycho correction